2003
DOI: 10.1002/mrm.10606
|View full text |Cite
|
Sign up to set email alerts
|

Normative pediatric brain data for spatial normalization and segmentation differs from standard adult data

Abstract: Spatial normalization and morphological studies of pediatric brain imaging data based on adult reference data may not be appropriate due to the developmental differences between the two populations. In this study, we set out to create pediatric templates and a priori brain tissue data from a large collection of normal, healthy children to compare it to standard adult data available within a widely used imaging software solution (SPM99, WDOCN, London, UK). Employing four different processing strategies, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 22 publications
4
132
0
2
Order By: Relevance
“…However, in some populations such as pediatric groups, individuals with disorders like schizophrenia, or healthy young or older adults, this could be problematic due to greater variability in anatomy as well as localization of functional activation (Brett et al, 2002;Park and Reuter-Lorenz, 2009). Thus approaches including population specific templates (Lee et al, 2005;Sanchez et al, 2012;Wilke et al, 2002Wilke et al, , 2003aWilke et al, , 2003bZhang et al, 2014) study-specific templates, or subject matched templates (Rohlfing et al, 2009) have been suggested instead (Huang et al, 2010;Padilla et al, 2011). However, these might prevent generalization of results across studies, and the need for such approaches has also been questioned given that depending on the resolution and population this may not pose a big problem (Burgund et al, 2002;Kang et al, 2003) and many standard templates may contain enough variability to cause concern (For review, see Evans et al (2012) and Mandal et al (2012)).…”
Section: Motion Correction During Data Processingmentioning
confidence: 99%
“…However, in some populations such as pediatric groups, individuals with disorders like schizophrenia, or healthy young or older adults, this could be problematic due to greater variability in anatomy as well as localization of functional activation (Brett et al, 2002;Park and Reuter-Lorenz, 2009). Thus approaches including population specific templates (Lee et al, 2005;Sanchez et al, 2012;Wilke et al, 2002Wilke et al, , 2003aWilke et al, , 2003bZhang et al, 2014) study-specific templates, or subject matched templates (Rohlfing et al, 2009) have been suggested instead (Huang et al, 2010;Padilla et al, 2011). However, these might prevent generalization of results across studies, and the need for such approaches has also been questioned given that depending on the resolution and population this may not pose a big problem (Burgund et al, 2002;Kang et al, 2003) and many standard templates may contain enough variability to cause concern (For review, see Evans et al (2012) and Mandal et al (2012)).…”
Section: Motion Correction During Data Processingmentioning
confidence: 99%
“…Any given imaging experiment will be better served by mapping to a population based atlas that closely resembles the cohort under study. We suggest that population atlases for groups such as Alzheimer's (Thompson et al, 2000); (Mega et al, 2005), schizophrenia ; (Cannon et al, 2006)), pediatric populations (Wilke et al, 2003); ; (Evans and Group, 2006)), autism (Joshi et al, 2004), even decades of life (Mazziotta et al, 2001) should be utilized, as appropriate, for the subject group.…”
Section: Group Statisticsmentioning
confidence: 99%
“…The object function used was normalized mutual information [9] and was maximized using Powell's golden search algorithm [10]. The pediatric brain template was available from Cincinnati Children's Hospital Medical Center (www.irc.cchmc.org) [7]. Templates are available for three age groups: young children (aged 5-9.5 years old), older children (aged 9.6-12.9 years old), and adolescents (aged 13-18.8 years).…”
Section: Mr Imagementioning
confidence: 99%
“…A pediatric atlas is needed because the human brain continues to develop throughout childhood and adolescence [6] and the use of an adult template in pediatric neuroimaging studies may introduce significant bias [7]. Kates et al [8] revised the original Talairach atlas grid to increase its applicability to pediatric brains.…”
Section: Introductionmentioning
confidence: 99%